The Impossible Dream: Tarn's Alexander in Retrospect - A. Brian Bosworth (Universitat Autònoma de Barcelona. Departament de Ciències de l’Antiguitat i l’Edat Mitjana., 2019)
In this great, although old and difficult to find, paper A. B. Bosworth review Tarn's work on Alexander and many of the Historiographical issues on Alexander the Great during most of the XXth Century.